Difference between revisions of "009A Sample Final 2, Problem 4"
Jump to navigation
Jump to search
(Created page with "<span class="exam">Use implicit differentiation to find an equation of the tangent line to the curve at the given point. ::<span class="exam"><math style="vertical-align: -4p...") |
|||
Line 21: | Line 21: | ||
|Using the product and chain rule, we get | |Using the product and chain rule, we get | ||
|- | |- | ||
− | | <math>6x+xy'+y+2yy'= | + | | <math>6x+xy'+y+2yy'=0.</math> |
|- | |- | ||
|We rearrange the terms and solve for <math style="vertical-align: -5px">y'.</math> | |We rearrange the terms and solve for <math style="vertical-align: -5px">y'.</math> | ||
Line 27: | Line 27: | ||
|Therefore, | |Therefore, | ||
|- | |- | ||
− | | <math>xy'+2yy'= | + | | <math>xy'+2yy'=-6x-y</math> |
|- | |- | ||
|and | |and | ||
|- | |- | ||
− | | <math>y'=\frac{ | + | | <math>y'=\frac{-6x-y}{x+2y}.</math> |
|} | |} | ||
Line 40: | Line 40: | ||
|- | |- | ||
| <math>\begin{array}{rcl} | | <math>\begin{array}{rcl} | ||
− | \displaystyle{m} & = & \displaystyle{\frac{ | + | \displaystyle{m} & = & \displaystyle{\frac{-6(1)-(-2)}{1-4}}\\ |
&&\\ | &&\\ | ||
− | & = & \displaystyle{ | + | & = & \displaystyle{\frac{4}{3}.} |
\end{array}</math> | \end{array}</math> | ||
|- | |- | ||
|Hence, the equation of the tangent line to the curve at the point <math style="vertical-align: -5px">(1,-2)</math> is | |Hence, the equation of the tangent line to the curve at the point <math style="vertical-align: -5px">(1,-2)</math> is | ||
|- | |- | ||
− | | <math>y= | + | | <math>y=\frac{4}{3}(x-1)-2.</math> |
|- | |- | ||
| | | | ||
Line 56: | Line 56: | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | | <math>y= | + | | <math>y=\frac{4}{3}(x-1)-2.</math> |
|} | |} | ||
[[009A_Sample_Final_2|'''<u>Return to Sample Exam</u>''']] | [[009A_Sample_Final_2|'''<u>Return to Sample Exam</u>''']] |
Latest revision as of 17:37, 14 September 2017
Use implicit differentiation to find an equation of the tangent line to the curve at the given point.
- at the point
Foundations: |
---|
The equation of the tangent line to at the point is |
where |
Solution:
Step 1: |
---|
We use implicit differentiation to find the derivative of the given curve. |
Using the product and chain rule, we get |
We rearrange the terms and solve for |
Therefore, |
and |
Step 2: |
---|
Therefore, the slope of the tangent line at the point is |
Hence, the equation of the tangent line to the curve at the point is |
Final Answer: |
---|